What Lies Behind the Students’ Need in English for Specific Purposes: A Reflection of Needs Analysis - Rachmawati, Umi (JOLLT Journal of Languages and Language Teaching, 2020)
This study was a need analysis study as a part of the research and development of instructional materials for English for Business (EFB) at Universitas Muhammadiyah Magelang. This study was aimed at finding the studentsâ€™ needs on their EFB course in terms of their personal characteristics, English proficiency assumption, learning motivation, and personal interest in their learning English. This study was conducted in a qualitative study that involved the nature of the qualitative study in nature. The findings of the study indicated that (1) the studentsâ€™ were adolescents that were ready and conscious to get the lesson, (2) the students felt that they did not have good English mastery, (3) the studentsâ€™ motivation in learning individually was not as high as learning in groups though they realized that they needed to master the target language, and (4) the studentsâ€™ preferred to have more topics on Islamic values and functions in English and teacherâ€™s roles are planner, information provider, and resource developer.Â Â